Video tutorial of the Crop Wild Relative Global Atlas - Crop Wild Relatives and Climate Change (2013)
Video tutorial of the Crop Wild Relatives Global Atlas, an online interactive map displaying the distributions and conservation concerns for the wild cousins of our cultivated crops. The three visualization modes are presented: searching by crop wild relative species; examining results by crop gene pool; and displaying the global summary of all results combined.